(untitled) (LEARNing Landscapes, 2014)
Concern for teachers at the beginning of their careers has been focused on retaining teachers and inducting them into fixed professional roles. This inquiry shifts the conversation to a perspective of sustaining them on the professional knowledge landscape while attending to individual identity. The experiences of one young woman named Anna opens conversation about the ways stories from her personal life shaped who she was in her classroom. This inquiry explores the need for continuity of experience as a key to continuing identity formation and sustaining teachers at the beginning of their careers.